2016
DOI: 10.18666/tpe-2016-v73-i3-6364
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Physical Literacy to Promote Healthy Lives: TGfU and Related Approaches

Abstract: The knowledge acquired in physical education classes should provide for an increase in physical activity and promote interest in healthier lifestyles. Despite the importance of physical literacy developed in physical education classes, physical education is not perceived as important, and funding for physical education has decreased. This paper highlights the importance of physical education on the development of competent, confident students by reviewing instructional approaches: The Teaching Games for Unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Pengetahuan dan pembelajaran yang diperolehi semasa di dalam kelas Pendidikan Jasmani perlu disediakan dengan lebih sistematik dan effektif kerana ia dapat menarik minat kanakkanak untuk melakukan aktiviti fizikal seterusnya meningkatkan penglibatan dalam aktiviti kecergasan fizikal dan mengalakkan minat dalam gaya hidup sihat (Doozan, & Bae, 2016). Sehubungan dengan itu, kajian yang berkaitan dengan pembelajaran dan program yang sistematik bagi subjek pendidikan jasmani amat kurang dijalankan (Chin, & Ludwig, 2013).…”
Section: Pernyataan Masalahunclassified
“…Pengetahuan dan pembelajaran yang diperolehi semasa di dalam kelas Pendidikan Jasmani perlu disediakan dengan lebih sistematik dan effektif kerana ia dapat menarik minat kanakkanak untuk melakukan aktiviti fizikal seterusnya meningkatkan penglibatan dalam aktiviti kecergasan fizikal dan mengalakkan minat dalam gaya hidup sihat (Doozan, & Bae, 2016). Sehubungan dengan itu, kajian yang berkaitan dengan pembelajaran dan program yang sistematik bagi subjek pendidikan jasmani amat kurang dijalankan (Chin, & Ludwig, 2013).…”
Section: Pernyataan Masalahunclassified
“…The knowledge and learning gained while in the Physical Education class needs to be provided more systematically and effectively. It can attract children to do physical activities, increasing involvement in physical fitness activities and encouraging interest in a healthy lifestyle (Doozan & Bae, 2016). Accordingly, systematic learning and programming studies for physical education subjects are very poorly conducted (Chin & Ludwig, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The body of research on the implementation of TGfU in PE is extensive. TGfU-based interventions carried out in different PE settings have shown the model’s positive impact on tactical awareness [ 25 ], decision making, enjoyment, and intention to be active [ 26 ], motivation and perceived competence [ 23 ], academic performance and literacy [ 27 ], movement skills [ 28 ], or PA levels [ 29 ]. Despite its widespread use in school PE, and although several studies have suggested that TGfU may not only trigger a significant development of the cognitive domain but also stimulate moderate-to-vigorous PA levels and higher motivation towards active lifestyles, the assessment of how TGfU school units influence physical fitness remains only marginally explored [ 30 ].…”
Section: Introductionmentioning
confidence: 99%